Fracture of the Fabella: A Rare Injury in Knee Trauma. (20th November 2012) - Barreto, Andre Rodrigues Façanha; Chagas-Neto, Francisco Abaete; Crema, Michel Daoud; Lorenzato, Mario Muller; Kobayashi, Mariana Tiemi Teixeira; Monteiro, Carlos Ribeiro; Nogueira-Barbosa, Marcello Henrique
Abstract : We present a case of a 21-year-old woman sustaining a traumatic [fabellar] fracture following a motor vehicle accident. The fabellar fracture was confirmed on plain films, which prompted further evaluation of the knee with ultrasound and magnetic resonance imaging to evaluate other possible associated injuries. Fracture of the fabella is a rare condition. Clinically, patients present with posterolateral knee pain, edema, and limited knee extension. Occasionally these symptoms may be very subtle, delaying the correct diagnosis and patient management.